2022
DOI: 10.3168/jds.2021-20721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound probiotics on growth performance, rumen fermentation, blood parameters, and health status of neonatal Holstein calves

Abstract: This study aimed to investigate the effects of compound probiotics (consisting of 10 8 cfu/g of Lactobacillus plantarum, 10 8 cfu/g of Pediococcus acidilactici, 10 8 cfu/g of Pediococcus pentosaceus, 10 7 cfu/g of and Bacillus subtilis) on growth performance, rumen fermentation, bacteria community, blood parameters, and health status of Holstein calves at the first 3 mo of age. Forty-eight newborn calves were randomly divided into the following 3 groups: control group (milk replacer with no compound probiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Serum biochemical parameters and antioxidant activity analysis were analyzed following the procedure of our previous study [ 18 ]. Briefly, after the samples thawed at 4 °C, the contents of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein (TP), albumin (ALB), creatinine (CERA), carbamide (UERA), uric acid (UA), glucose (GLU), total cholesterol (T-CHO), triglyceride (TG), and alkaline phosphatase (ALP) were determined using Hitachi 3100 (Hitachi Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Serum biochemical parameters and antioxidant activity analysis were analyzed following the procedure of our previous study [ 18 ]. Briefly, after the samples thawed at 4 °C, the contents of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein (TP), albumin (ALB), creatinine (CERA), carbamide (UERA), uric acid (UA), glucose (GLU), total cholesterol (T-CHO), triglyceride (TG), and alkaline phosphatase (ALP) were determined using Hitachi 3100 (Hitachi Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The probiotic was given to calves throughout their first month of life, and it enhanced their gut microbiota and growth performance, as well as some biometric parameters [41]. Hence, a high quantity of compound probiotics is suggested to progress rumen development and health status of Holstein calves [82]. It has been reported that probiotics containing Bacillus spores and nucleotides had no synergistic impact on calves' development, welfare, or fecal bacteria; however, nucleotide supplementation reduces Lactobacillus feces levels [83].…”
Section: Application Of Probiotics In In Vivo Studies For Ruminant Pr...mentioning
confidence: 99%
“…Likewise, MR can positively affect calf rumen development ( 59 ). Interestingly, most studies have focused on the effects of combining milk replacer with other beneficial supplements, such as probiotics and milk replacer, on the calf rumen ( 60 , 61 ). Indeed, a study found that adding probiotics to MR improved rumen development ( 61 ).…”
Section: Effect Of Wm Feeding On Calf Performancementioning
confidence: 99%